Evaluation of the basal temperature of snow (BTS) method to map permafrost in complex mountainous terrain, Wolf Creek, Yukon Territory - Ednie, Mark (University of Ottawa (Canada), 2003)
This study is the first known attempt in North America to use the basal temperature of snow (BTS) method to predict the distribution of mountain permafrost. The study site, Wolf Creek Research Basin, Yukon Territory (60°30'N, 135°13'W), is a 195 km2 basin ranging in elevation from 650--2100 m with a mean annual air temperature of about -4°C at 1235 m a.s.l. A modeled BTS surface, based on 394 measured BTS values and with elevation and potential incoming solar radiation as independent variables, was created within a GIS environment with an r2 value similar to European results. The distribution of permafrost within the basin was identified from pits and boreholes. A subsequent logistic regression was used to compare modeled BTS values to the actual permafrost distribution in order to produce a map of permafrost probability in the basin. A significantly higher likelihood of permafrost, observed in a confined valley bottom, was attributed to cold air drainage. This occurrence was not predicted by the BTS model and data from the affected area were removed from later analyses. (Abstract shortened by UMI.)
Keywords: Physical Geography.